2002
DOI: 10.1053/jhep.2002.33156
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of transarterial lipiodol chemoembolization for unresectable hepatocellular carcinoma

Abstract: This randomized, controlled trial assessed the efficacy of transarterial Lipiodol (Lipiodol Ultrafluide, Laboratoire Guerbet, Aulnay-Sous-Bois, France) chemoembolization in patients with unresectable hepatocellular carcinoma. From March 1996 to October 1997, 80 out of 279 Asian patients with newly diagnosed unresectable hepatocellular carcinoma fulfilled the entry criteria and randomly were assigned to treatment with chemoembolization using a variable dose of an emulsion of cisplatin in Lipiodol and gelatin-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

31
1,548
8
37

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,383 publications
(1,624 citation statements)
references
References 32 publications
31
1,548
8
37
Order By: Relevance
“…In 2002, two prospectively RCTs have demonstrated a significant survival benefit from TACE in selected HCC patients with preserved liver function and adequate performance status [331,332]. A subsequent meta-analysis confirmed these findings [333].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2002, two prospectively RCTs have demonstrated a significant survival benefit from TACE in selected HCC patients with preserved liver function and adequate performance status [331,332]. A subsequent meta-analysis confirmed these findings [333].…”
Section: Transarterial Chemoembolizationmentioning
confidence: 95%
“…In two RCTs and one systematic review with meta-analysis, TACE was found to improve survival compared with supportive care in patients with unresectable HCC [331][332][333]. Untreated patients at an intermediate stage present a median survival of 16 months.…”
Section: Transarterial Chemoembolizationmentioning
confidence: 96%
See 1 more Smart Citation
“…(7)(8)(9)(10)(11)(12)(13) These metaanalyses identified a distinct survival benefit for lipiodol TACE with cisplatin or doxorubicin compared to best supportive care. (14,15) As a result, Lipiodol TACE has been recommended as the standard of care for the treatment of unresectable, large, or multinodular noninvasive tumors isolated to the liver in patients who have neither evidence of hepatic decompensation nor cancer-related symptoms, that is, those cases classified as intermediate stage according to the Barcelona Clinic for Liver Cancer (BCLC) staging system.…”
mentioning
confidence: 99%
“…In selected patients with unresectable, liver-only, disease hepatic embolisation or chemoembolisation confers a survival advantage compared with conservative management (Llovet et al, 2002;Lo et al, 2002). However, in the recent meta-analysis, this effect may be limited to chemoembolisation but not embolisation .…”
mentioning
confidence: 99%